2022
DOI: 10.1111/jfpp.16609
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in emerging techniques for freezing and thawing on aquatic products' quality

Abstract: Aquatic products are favored by the majority of consumers because of their low fat, high protein, particularly low cholesterol. In recent years, consumers are demanding the high nutrition, freshness, and safety of aquatic products. Therefore, efficient preservation technologies are all important. Freezing can extend the shelf life and inhibit the seasonal fluctuations in different species. Thawing is an important step for aquatic products. Repeated freezing-thawing usually occurs because of the imperfection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 135 publications
(257 reference statements)
0
1
0
Order By: Relevance
“…Nowadays, seafood is favored by consumers because of its low-fat content, high-quality protein content, and low cholesterol. 1 The potential health benefits of a seafood-rich diet have been demonstrated as early as 1980, 2 and a high intake of seafood is associated with a reduction in some obesity-related chronic diseases such as cardiovascular disease and diabetes. 3 Studies have also shown that seafood intake has beneficial effects such as regulation of metabolic syndrome and inflammation in the body, 4 and n-3 polyunsaturated fatty acids (n-3 PUFAs) are important components of fish that play a role in exerting these effects.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, seafood is favored by consumers because of its low-fat content, high-quality protein content, and low cholesterol. 1 The potential health benefits of a seafood-rich diet have been demonstrated as early as 1980, 2 and a high intake of seafood is associated with a reduction in some obesity-related chronic diseases such as cardiovascular disease and diabetes. 3 Studies have also shown that seafood intake has beneficial effects such as regulation of metabolic syndrome and inflammation in the body, 4 and n-3 polyunsaturated fatty acids (n-3 PUFAs) are important components of fish that play a role in exerting these effects.…”
Section: Introductionmentioning
confidence: 99%